ALGORITHM FOR PHONOGRAM COMPARISON IN E-LEARNING SYSTEMS - V. V. Kiselev; A. G. Davydau; A. A. Tkachenia (Informatika)
An algorithm for determination of the degree of phonogram matching on the basis of linear spectral frequency and dynamic time warping is considered. The problem of phonogram comparison is handled as the problem of recognizing the analyzed speech signal, which contains a lot of distortion and noise with unknown beginning and duration, non-linear timescale, and unknown pronunciation sample. A functional diagram of the algorithm is presented.